Fire Risk Exposure and Preparedness of Peri-Urban Neighbourhoods in Ibadan, Oyo State, Nigeria. Issue 1 (February 2021) - Oloke, O.C.; Oluwunmi, O.A.; Oyeyemi, K.D.; Ayedun, C.A.; Peter, N.J.
Abstract: This study assessed the exposure of urban neighbourhoods to environmental hazards generally and fire risk in particular in Ibadan. Lagelu, a rapidly urbanizing local government area was selected for the study with emphasis on Lagelu West Local Development Council. Relevant literatures were review in this regards while structured questionnaires were administered on adult residents of 320 households in the selected peri-urban communities. Respondents opinion were obtained as regards the susceptibility of their communities to different environmental hazards. Data was also obtained from the respondents on the causes/sources of fire risk in their respective neighbourhoods as well as adequacy of fire safety apparatus in the communities. Data were measured on 5-Point likert scale of strongly agreed (5) to strongly disagree (1). Response were analysed with basic tools of mean score, relative importance and interpreted based on cut-off point (as devised in Morenikeji, 2006). The causes of fire and adequacy of community fire safety apparatus were analysed in percentages and presented in tables and bar charts. The study showed that there is a general consensus that the communities are highly vulnerable to the environmental risks identified in the study. It was also revealed that fire outbreak is principally caused by human activities, negligence as well as faulty electrical equipment and power surge. Respondents generally are of the opinion that fire safety apparatus available in the communities are grossly inadequate thereby compounding the vulnerability predicament of these communities. The study therefore recommends amongst others, upgrade of the community road network, provision of firefighting system within the neigbhourhood and enlightenment of residents on fire safety precautions.